Faktor Yang Berhubungan Dengan Motivasi Perawat Untuk Melanjutkan Pendidikan Pada Jenjang Pendidikan Tinggi Keperawatan di Ruang Instalasi Rawat Inap RS Tk II Pelamonia Makassar - Andi Muhammad Adam Aminuddin (Unit Publikasi Ilmiah Perkumpulan Intelektual Madani Indonesia, 2021)
Nurses in Indonesia have the highest number when compared to other health workers, so their role is a determinant in improving the quality of health services both at Puskesmas and at the Ministry of Health Hospital 2016. According to South Sulawesi Province, the number of nurses in 2016 recorded through health profiles was 109.52% of people. from various educational strata. This study was to identify factors related to the motivation of nurses to continue education at the level of higher nursing education at the TK II Pelamonia Hospital Makassar. Based on the research objectives, the research design used an analytic cross sectional, where the researcher observed or measured variables at one time (point time approach). The results showed that there was a relationship between age and motivation to continue education at the nursing higher education level. There is a relationship between supervisor support and motivation to continue education at the nursing higher education level, where the chi_square statistical test shows that the significance value = 0.037 (? < 0.050), then Hi is accepted and Ho is rejected. The dominant factor related to motivation to continue education at the nursing higher education level is the age factor where the chi_square statistic test shows a significance level of = 0.009, indicating a high degree of association